Counterblasting Canada : Marshall McLuhan, Wyndham Lewis, Wilfred Watson, and Sheila Watson - Betts, Gregory, 1975- (The University of Alberta Press, 2016)
"In 1914, Ezra Pound and Wyndham Lewis--the founders of Vorticism--undertook an unprecedented analysis of the present, its technologies, communication, politics, and architecture. The essays in Counterblasting Canada trace the influence of Vorticism on Marshall McLuhan and Canadian Modernism. Building on the initial accomplishment of Blast, McLuhan's subsequent Counterblast, and the network of artistic and intellectual relationships that flourished in Canadian Vorticism, the contributors offer groundbreaking examinations of postwar Canadian literary culture, particularly the legacies of Sheila and Wilfred Watson. Intended primarily for scholars of literature and communications, Counterblasting Canada explores a crucial and long-overlooked strand in Canadian cultural and literary history. Contributors: Gregory Betts, Adam Hammond, Dean Irvine, Elena Lamberti, Philip Monk, Linda Morra, Kristine Smitka, Leon Surette, Paul Tiessen, Adam Welch, Darren Wershler."--